ANAMOLIES IN INDIAN STOCK MARKET - Tandon, Dr Chand (The journal of contemporary issues in business and government, 2022)
The efficient-market hypothesis (EMH) is unique and necessary economic and money hypotheses that are tested over the past century. Because of many abnormal phenomena and conflicting proof, otherwise referred to as anomalies against EMH, some intellectuals have questioned whether or not EMH is valid, and has substantial proof of anomalies, so several theories are developed to clarify some anomalies. This review is helpful to Intellectuals for developing up-to-date treatments of monetary theory that EMH, anomalies, and behavioral Finance underlie. The review is additionally useful to investors for creatingselections of investment merchandise and methods that suit their risk preferences and behavioural traits foreseen from behavioural models. Finally, when EMH, anomalies and behavioural Finance square measure wont to justify the impacts of capitalist behaviour on stock value movements, it’s priceless to policy manufacturers, once reviewing their policies, to avoid excessive fluctuations available markets.